Two homozygous adjacent novel missense mutations in DYSF gene caused dysferlinopathy due to splicing abnormalities - Wang, Lun; Zhou, Yan; Wei, Tiantian; Huang, Hongyao (Frontiers in Genetics, 2024)
Background: Dysferlinopathy was an autosomal recessive disorder caused by mutations in the DYSF gene. This study reported two homozygous adjacent missense mutations in the DYSF gene, presenting clinically with bilateral lower limb weakness and calf swelling. Two homozygous adjacent missense mutations in the DYSF gene may be associated with the development of Dysferlinopathy, but the exact mechanism needs to be further investigated.A retrospective analysis of clinical data from a Dysferlinopathy-affected family was conducted. Peripheral blood samples were collected from members of this family for whole-exome sequencing (WES) and copy number variation analysis. And Sanger sequencing was employed to confirm potential pathogenic variants. Human Splicing Finder (HSF), SpliceAI, and Varseak database were used to predict the effect of mutations on splicing function. The pathogenic mechanism of aberrant splicing in Dysferlinopathy due to two homozygous adjacent missense mutations in the DYSF gene was determined by splicing assay in vivo and minigene assay in vitro.: The proband was a 42-year-old female, who presented with weakness of lower limbs for 2 years, edema of lower leg. Two homozygous DYSF variant c.5628C>A p.D1876E and c.5633A>T p.Y1878F phenotype in this family were identified in the proband. Bioinformatics databases suggested that the mutation c.5628C>A of DYSF had no significant impact on splicing signals. HSF suggested that the mutation c.5633A>T of DYSF alteration of auxiliary sequences, significant alteration of ESE/ESS motif ratio. Varseak and SpliceAI suggested that the mutation c.5633A>T of DYSF had no splicing effect. Both splicing in vivo and minigene assay in vitro showed two adjacent mutations c.5628C>A p.D1876E and c.5633A>T p.Y1878F in DYSF gene lead to Exon50 jump, and resulted in a 32aa amino acid deletion within the protein. Point mutation c.5628C>A p.D1876E in DYSF affected splicing in vitro, while point mutation c.5633A>T p.Y1878F in DYSF gene did not affect splicing function. Conclusion: This study confirmed for the first time that two homozygous mutations of DYSF were associated with the occurrence of dysferlinopathy. The c.5628C>A p.D1876E mutation in DYSF affected splicing function and may be one of the contributing factors to the pathogenicity.